Numerical Investigations on Charging/Discharging Performance of a Novel Truncated Cone Thermal Energy Storage Tank on a Concentrated Solar Power System. (27th January 2019) - Mao, Qianjun; Liu, Ning; Peng, Li
Abstract : Developing a concentrated solar power (CSP) technology is one of the most effective methods to solve energy shortage and environmental pollution all over the world. Thermal energy storage (TES) system coupling with phase change materials (PCM) is one of the most significant methods to mitigate the intermittence of solar energy. In this paper, firstly, a 2D physical and mathematical model of a novel truncated cone shell-and-tube TES tank has been proposed based on enthalpy method. Secondly, the performance during the charging/discharging process of the truncated cone tank has been compared with the traditional cylindrical tank. Finally, the effects of inlet conditions of heat transfer fluid (HTF), and thickness of tube on the charging/discharging process, stored/released energy capacity; energy storage/release rate and heat storage efficiency have been investigated. The results show that the performance of truncated cone tank is better, and the charging/discharging time reduces 32.08% and 21.59%, respectively, compared with the cylindrical tank. The effect of wall thickness on the truncated cone TES tank can be ignored. And the inlet temperature and velocity of HTF have the significant influence on the charging/discharging performance of TES tank. And the maximum heat storage efficiency of the truncated cone TES tank can reach 93%. However, some appropriate methods should be taken for improving the thermal energy utilization rate of HTF in the future. This research will provide insights and significant reference towards geometric design and operating conditions in TES system.